Memperjuangkan Keluarga Sakinah di Tengah Era Globalisasi di Indonesia - Fatimah Zuhrah (Journal of Gender and Social Inclusion in Muslim Societies, 2022)
In general, the commitment, vision, and expectation of husbands and wives when they married were to manifest, and present a sakinah, Mawaddah, and rahmah household life. Marriage is very relevant to the effort to realize and get the success and happiness of household which means sakinah, but the reality of marriage is only as a lifestyle trend now. Marriage is nothing more than a staging of luxury that is far from religious values, resulting in an initially immortal and sacred marriage to be a conventional activity. This phenomenon is evident from the divorce rate until now fairly high. Sakinah family is unlikely to emerge for an instant but arises because of the process of husband and wife. Sakinah in the family come is due to the process and patience of husband and wife in fostering the household, and also through the sacrifice and strength of the soul. With a process of patience, the gift will also be given by God as the highest form of love in the family. Thus, some processes in creating a sakinah family are: Creation of a religious life in the family, the time to gather with family, have good communication between family members. Mutual respect among fellow family members, Quality and quantity of conflict is minimal, and The existence of a close relationship or bond between family members.